CATHODOLUMINESCENCE AND LASER-EXCITED LUMINESCENCE SPECTROSCOPY OF EU3+ AND EU2+ IN SYNTHETIC CAF2: A COMPARATIVE STUDY - Barbin V.; Jouart J.P.; Dalmeida T. (My University, 1996)
A comparative study of laser-excited luminescence and cathodoluminescence of CaF2:0.1 % EuF3 at room temperature was performed to determine the position and relative intensity of Eu3+ and Eu2+ main emission lines in CaF2. Cathodoluminescence spectra show a major peak at 424 nm which is related to the electric dipole allowed 4f65d-4f7 transition of the Eu2+ ion. The cathodoluminescence peaks of the Eu3+ ion are very weak and are not easily identifiable. Photoluminescence spectra recorded under different laser excitation conditions (corresponding to the 7F0 →a- 5D0 transition of the Eu3+ ion) reveal major peaks around 590 nm due to the magnetic dipole allowed 7F0 → 5D1 transition of the Eu3+ ion in three different environments: tetragonal, dimer and cubic. We emphasize the necessity of using a tunable laser to unambiguously identify the Eu3+ ions in the minerals.